2019
DOI: 10.1029/2019gl083499
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Crustal Magnetic Fields and Solar EUV Flux on Ionopause Formation at Mars

Abstract: We study the ionopause of Mars using a database of 6,893 ionopause detections obtained over 11 years by the MARSIS (Mars Advanced Radar for Subsurface and Ionosphere Sounding) experiment. The ionopause, in this work, is defined as a steep density gradient that appears in MARSIS remote sounding ionograms as a horizontal line at frequencies below 0.4 MHz. We find that the ionopause is located on average at an altitude of 363±65 km. We also find that the ionopause altitude has a weak dependence on solar zenith an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 53 publications
3
30
0
Order By: Relevance
“…The ionopause altitude above the strong crustal fields is higher on the dayside, by more than 200 km for some SZA ranges. This result is also consistent with Garnier et al (2017), who showed that the altitude of the PEB depends strongly on the crustal magnetic fields, which increase the altitude on average by about 150 km, and with Chu et al (2019) who found that the crustal magnetic fields increase the altitude of the ionopause by ~1.58 km per nT.…”
Section: Effect Of the Crustal Fields On The Occurrence And The Altitsupporting
confidence: 91%
See 4 more Smart Citations
“…The ionopause altitude above the strong crustal fields is higher on the dayside, by more than 200 km for some SZA ranges. This result is also consistent with Garnier et al (2017), who showed that the altitude of the PEB depends strongly on the crustal magnetic fields, which increase the altitude on average by about 150 km, and with Chu et al (2019) who found that the crustal magnetic fields increase the altitude of the ionopause by ~1.58 km per nT.…”
Section: Effect Of the Crustal Fields On The Occurrence And The Altitsupporting
confidence: 91%
“…The occurrence rate is slightly less near the poles; however, the difference is not very significant. Considering the data coverage is homogeneous with respect to geographic longitude (Chu et al, 2019), we find no evidence for an inhomogenous distribution of ionopause locations. We find that the ionopause occurs with approximately the same frequency at all latitudes and longitudes.…”
Section: Location Of the Ionopausementioning
confidence: 49%
See 3 more Smart Citations